Analisis Manajemen Risiko Sistem Informasi Akuntansi Pada PT. Batu Bara XYZ ISO 31000:2018 - Afifah Azzahra; Putra Aditya; Sri Andayani (ITB Ahmad Dahlan Jakarta, 2024)
This study employs the ISO 31000:2018 framework to manage the accounting information system risks at PT. Batu Bara XYZ. It identifies, analyzes, evaluates, and treats risks accordingly. The findings reveal that classifying risks based on their likelihood and impact assists the company in planning effective risk management strategies. The implementation of the ISO 31000:2018 framework enables the company to better manage risks and enhance information security. The research aims to analyze the risk management of the accounting information system at PT. Batu Bara XYZ using the ISO 31000:2018 framework. A case study and quantitative approach were utilized as research methods. The study results demonstrate the identification, analysis, and evaluation of various potential risks affecting the company's accounting information system. This research is expected to provide insights into best practices and challenges faced, as well as offer recommendations for future risk management improvements.